Suppression of Survival Signalling Pathways by the Phosphatase PHLPP - O'Neill, Audrey K. (2012)
The recently discovered PH (pleckstrin homology) domain Leucine rich repeat Protein Phosphatase (PHLPP) family is emerging as a central component in suppressing cell survival pathways. Originally discovered in a rational search for a phosphatase that directly dephosphorylates and inactivates Akt, PHLPP is now known to potently suppress cell survival both by inhibiting proliferative pathways and by promoting apoptotic pathways. In the first instance, PHLPP directly dephosphorylates a conserved regulatory site (termed the hydrophobic motif) on Akt, protein kinase C (PKC), and S6 kinase, thereby terminating signalling by these pro-survival kinases. In the second instance, PHLPP dephosphorylates and thus activates the pro-apoptotic kinase Mst1, thereby promoting apoptosis. PHLPP is deleted in a large number of cancers and the genetic deletion of one isozyme in a PTEN (phosphatase and tensin homolog located on chromosome 1) +/− prostate cancer model results in increased tumourigenesis, underscoring the role of PHLPP as a tumour suppressor. This review summarises the targets and cellular actions of PHLPP, with emphasis on its role as a tumour suppressor in the oncogenic PI3K (phosphoinositide 3-kinase)/Akt signalling cascade.